Cleavage cascade of the sigma regulator FecR orchestrates TonB-dependent signal transduction - Tatsuhiko Yokoyama; Ryoji Miyazaki; Takehiro Suzuki; Naoshi Dohmae; Hiroki Nagai; Tomoya Tsukazaki; Tomoko Kubori; Yoshinori Akiyama (Proceedings of the National Academy of Sciences, 2025)
TonB-dependent signal transduction is a versatile mechanism observed in gram-negative bacteria that integrates energy-dependent substrate transport with signal relay. In Escherichia coli , the TonB–ExbBD motor complex energizes the TonB-dependent outer membrane transporter FecA, facilitating ferric citrate import. FecA also acts as a sensor, transmitting signals to the cytoplasmic membrane protein FecR, which eventually activates the cytoplasmic sigma factor FecI, driving transcription of the fec operon. Building on our previous finding that FecR undergoes functional maturation through a three-step cleavage process [T. Yokoyama et al., J. Biol. Chem. 296 , 100673 (2021)], we here describe the complete mechanism of FecR-mediated ferric citrate signaling involving FecA and TonB. The cleavage cascade begins with FecR autoproteolysis prior to membrane integration. The soluble C-terminal domain (CTD) fragment of FecR is cotranslocated with the N-terminal domain (NTD) fragment through a twin-arginine translocation (Tat) system–mediated process. In the periplasm, the interaction between the CTD and NTD fragments prevents further cleavage. Binding of ferric citrate induces a conformational change in FecA, exposing its TonB box to the periplasmic space. This structural alteration is transmitted to the interacting FecR CTD via the motor function of TonB, resulting in the release of the CTD blockage from the NTD. Consequently, the successive cleavage of FecR’s NTD is initiated, culminating in the ferric citrate signal–induced activation of fec gene expression. Our findings reveal that the regulation of FecR cleavage, controlled by the TonB–FecA axis, plays a central role in the bacterial response to ferric citrate signals.